The study on effect of crossing waypoints on tactical distance separation - Chua, Zheng Hong (2018)
This project aims to present a new concept, Distance Separation Level (DSL), to value add on future research on the Air Traffic Controller (ATC) in the dynamic and rapid-growing landscape of Air Traffic Management (ATM). The aviation industry is expected to grow at a tremendous rate in the coming decades. This is due to the growth of income of the average family and the increased affordability of air fare which allow more people to travel. The present ATM system help the aviation industry progress to what it is today. However, with the continuous growth of the aviation industry, the current ATM system might not be sufficient for the projected growth and future studies in the coming decades. With that in mind, the workload of the ATC will be intensified, thus incurring stresses and increase the risk of air traffic accidents. Despite the growing air traffic density, the safety of the airspace should not be compromised. Any errors could result in catastrophic accidents. Therefore, ATC still play an important role in maintaining airspace safety, to ensure passengers remain safe for all flights. As a result, more research should be conducted to improve the ATC efficiency and capability. Due to the limitations of current ATM complexity models and ATM mental research studies, more research should be conducted to study how the airspace complexity could affect the overall performance of the ATC. As such, the motivation of this project is to utilise the Distance Separation Level (DSL) model to study the various effect of crossing points on tactical distance separations. Through this study, the author hopes to better comprehend how the DSL model behaves with different traffic scenario. Aircraft flight route have been capture into intervals to determine the different DSL. Findings were then established, which could be used as a basis for characterisation of crossing points and further research. A safety net can be determined for the new concept is as effective as it is designed for this study.